Advanced Oxidation Processes: An Effective Solution for Treating Emerging Pollutants from Pharmaceutical Industries - Vijaya Kumar Mamilla (E3S Web of Conferences)
The rapid increase in population poses a grave threat to environmental sustainability and water availability. India's pharma industry holds the 3rd position globally in pharmaceutical production by volume. However, the industry's wastewater contains harmful substances such as high concentrations of organic matter, microbial toxicity, salts, and non-biodegradable compounds, posing a significant danger to human health and the ecosystem. Regularly assessing wastewater discharge against regulatory standards is vital to ensure water safety. The presence of emerging contaminants in natural and drinking water directly jeopardises water quality and the survival of aquatic life. Advanced treatment methods are imperative, as trace amounts of solids and organic matter can persist even after secondary treatment. Treating pharmaceutical wastewater is particularly challenging due to the wide variety of products produced in the industry. The Advanced Oxidation Process is a highly effective technology for removing pollutants from wastewater. It is crucial to implement safe and effective treatment methods to mitigate the impact of pharmaceutical wastewater. This paper critically evaluates AOPs and their ability to treat pharmaceutical wastewater, providing valuable insights into pharmaceutical industry wastewater, the significance and characteristics of pharmaceutical wastewater, their impact on human health and the ecosystem, various treatment methods, and different AOPs employed for treating pharmaceutical wastewater in detail.